Multiplex Real-Time PCR Assay for Rapid Detection of Methicillin-Resistant Staphylococci Directly from Positive Blood Cultures - Wang, Hye-young (American Society for Microbiology, 2014)
Methicillin-resistant Staphylococcus aureus (MRSA) is the most prevalent cause of bloodstream infections (BSIs) and is recognized as a major nosocomial pathogen. This study aimed to evaluate a newly designed multiplex real-time PCR assay capable of the simultaneous detection of mecA, S. aureus, and coagulase-negative staphylococci (CoNS) in blood culture specimens. The Real-MRSA and Real-MRCoNS multiplex real-time PCR assays (M&D, Republic of Korea) use the TaqMan probes 16S rRNA for Staphylococcus spp., the nuc gene for S. aureus, and the mecA gene for methicillin resistance. The detection limit of the multiplex real-time PCR assay was 10(3) CFU/ml per PCR for each gene target. The multiplex real-time PCR assay was evaluated using 118 clinical isolates from various specimen types and a total of 350 positive blood cultures from a continuous monitoring blood culture system. The results obtained with the multiplex real-time PCR assay for the three targets were in agreement with those of conventional identification and susceptibility testing methods except for one organism. Of 350 positive bottle cultures, the sensitivities of the multiplex real-time PCR kit were 100% (166/166 cultures), 97.2% (35/36 cultures), and 99.2% (117/118 cultures) for the 16S rRNA, nuc, and mecA genes, respectively, and the specificities for all three targets were 100%. The Real-MRSA and Real-MRCoNS multiplex real-time PCR assays are very useful for the rapid accurate diagnosis of staphylococcal BSIs. In addition, the Real-MRSA and Real-MRCoNS multiplex real-time PCR assays could have an important impact on the choice of appropriate antimicrobial therapy, based on detection of the mecA gene.